2018
DOI: 10.1080/14781700.2018.1543613
|View full text |Cite
|
Sign up to set email alerts
|

Automation anxiety and translators

Abstract: Translation is currently described as a profession under pressure from automation, falling prices and globalized competition. Translators' stance on machine translation (MT) is famously negative, but the economic dimension of this positioning is scarcely researched and often unclear. This article provides an analysis of translators' blog and forum postings contextualized within general trends in employment, the economy and work automation. The analysis concentrates on MT and pay. Two key findings are reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 24 publications
0
17
0
5
Order By: Relevance
“…Moorkens and O'Brien 2015;Läubli and Orrego-Carmona 2017). This can be associated with MT's unsuitability for certain tasks (Cadwell et al 2017) as well as with broader issues linked to the economy and the structure of the translation industry (Vieira 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Moorkens and O'Brien 2015;Läubli and Orrego-Carmona 2017). This can be associated with MT's unsuitability for certain tasks (Cadwell et al 2017) as well as with broader issues linked to the economy and the structure of the translation industry (Vieira 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This implies situations where MT use is not inherent to the commission, which is a different context from the one discussed here, where MT use was for the most part an open requirement or request. 2 Previous research by one of the present authors has found that negative attitudes to MT in professional communities are usually more directly linked to business issues and the technology's impact on the market rather than to the notion that MT may outperform human translators (Vieira, 2018). Importantly, this places emphasis on the practices that surround MT use rather than on MT itself as a focus of discussion, a standpoint that serves as backdrop for the work presented here.…”
Section: Previous Research On Attitudes To Mtmentioning
confidence: 83%
“…The hype about neural MT (NMT) (Castilho et al 2017) has brought existential angst to the fore for translators (Vieira 2018). On the face of it, the large and growing amounts of translation required should mean that both human and machine translation have a strong outlook.…”
Section: Ai and The Future Of Translation Work: Machine Translation And Human Wisdommentioning
confidence: 99%